Improved plant yield efficiency alleviates the erratic optimum density in maize. (14th April 2020) - Mylonas, Ioannis; Sinapidou, Evaggelia; Remountakis, Emmanouel; Sistanis, Iosif; Pankou, Chrysanthi; Ninou, Elissavet; Papadopoulos, Ioannis; Papathanasiou, Fokion; Lithourgidis, Anastasios; Gekas, Fotakis; Dordas, Christos; Tzantarmas, Constantinos; et al.
Abstract: Plant yield efficiency (PYE) reflects the ability of the single‐plant to respond to additional inputs and is fully expressed at the nil ‐competition regime (an ultra‐low density to preclude inter‐plant interference for inputs). The purpose of this study was to determine if PYE could prevent the erratic optimum plant density–yield interaction effect in maize ( Zea mays L.). Seven hybrids were evaluated across five environments at four densities, under both the normal‐input regime (NIR) and low‐input regime (LIR). Plant yield efficiency was measured at the lowest density approaching the nil ‐competition regime (0.74 plants m –2 ), while crop (per area) yield potential was estimated at the highest density corresponding to the typical farming density in the NIR (8.89 plants m –2 ). In terms of optimum density, the hybrids varied extensively in the NIR (6.64–8.81 plants m –2 ) but performed similarly in the LIR (5.11–5.61 plants m –2 ). The hybrid displaying the highest PYE also had high harvest index (HI) and low anthesis to silking interval (ASI) and was proved the most stable according to various stability statistics including the genotype and genotype by environment (GGE) biplot model. In conclusion, crop yield by density interaction is a matter of hybrid. Hybrids with low PYE have inconsistent optimum density, which is a causal factor of yield loss in rainfed maize. High PYE improves hybrid flexibility and performance at low densities ultimately enhancing crop resilience to extremely fluctuating environments.